2022
DOI: 10.2188/jea.je20210271
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Progress and Evaluation of the Thyroid Ultrasound Examination Program, the Fukushima Health Management Survey

Abstract: The Great East Japan Earthquake on March 11, 2011, and the subsequent tsunami caused an accident at the Fukushima Daiichi Nuclear Power Plant, in which extensive damage to the nuclear power reactors resulted in massive radioactive contamination. Fukushima Prefecture implemented the Thyroid Ultrasound Examination (TUE) program as part of the Fukushima Health Management Survey project in response to residents’ anxieties about health risks due to radiation exposure for residents aged 0–18 years at the time of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…As of June 30, 2020, a total of 246 examinees in the baseline, 2 nd , 3 rd , and 4 th survey at aged 25 years were determined to have nodules cytologically diagnosed as malignant or suspicious for malignancy. 8 …”
Section: Outcomes and Follow-up: Summary Of The Results Of The Fhmsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of June 30, 2020, a total of 246 examinees in the baseline, 2 nd , 3 rd , and 4 th survey at aged 25 years were determined to have nodules cytologically diagnosed as malignant or suspicious for malignancy. 8 …”
Section: Outcomes and Follow-up: Summary Of The Results Of The Fhmsmentioning
confidence: 99%
“…Protocols in the FHMS have been reported elsewhere. 1 , 6 In brief, the FHMS consists of the Basic Survey 7 and four detailed surveys: the Thyroid Ultrasound Examination, 8 Comprehensive Health Check, 9 Mental Health and Lifestyle Survey, 10 and Pregnancy and Birth Survey (Figure 1 ). 11 , 12 The eligible population of the Basic Survey was mainly individuals registered as residents in Fukushima Prefecture between March 11 and July 1, 2011 (including evacuees) and residents of other prefectures who commute to Fukushima Prefecture, totaling approximately 2.05 million people.…”
Section: Main Features and Participants: Overview Of The Fhms Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, primary examination of the Thyroid Ultrasound Examination (TUE) program conducted in FP in 2011-2013, and included 367,649 subjects (81.7% coverage)) who were generally ≤ 18 years old and living in FP at the time of the disaster. Conducting the TUE immediately after the GEJE enabled comparison of the obtained results with subsequent occurrence of thyroid cancer (5). Thereafter, primary examinations of TUE were conducted every two years until the examined individual was ≥ 20 years, with milestone examinations conducted every ve years thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the results of the second- (fiscal years 2014–2015) and third- (fiscal years 2016–2017) rounds of the survey (Full-scale Survey) have been finalised. 11 Using the results of the second-round survey, two studies reported no statistically significant association between the estimated radiation dose and thyroid cancer diagnosis. 12 , 13 Some studies also indicated that the detection rates of thyroid cancer in the second-round survey were associated with the mean external radiation dose in air based on published regional counts of thyroid cancer cases, 14 , 15 although the results could not be adjusted for the age at diagnosis and prevalence and incidence could not be distinguished.…”
Section: Introductionmentioning
confidence: 99%